2016
DOI: 10.1111/ajgw.12256
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antibrowning and antioxidant activities in unripe grapes recovered during bunch thinning

Abstract: Background and Aims: Research into new systems for controlling enzymatic browning in the agro-food industry has been focused on eco-friendly alternatives to conventional thermal treatments and traditional additives, which could impair the sensory, nutritional and health properties. The use of unripe grapes for reducing alcohol concentration and pH of wines has been previously reported; however, no studies have been made of the evaluation of unripe grapes as potential functional ingredients to control enzymatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 42 publications
2
46
0
Order By: Relevance
“…A potential use of unripe grapes in winemaking to reduce the alcohol concentration and pH of wine was investigated by other authors, who observed a partial reduction of alcohol content and simultaneous decrease of pH of both Cabernet Sauvignon and Merlot experimental wines [ 12 ]. Although the bioactive compounds and antioxidant activities of grapes at maturity and by-products of the wine production chain have been the subject of many investigations, unripe grapes and their potential application in the food industry have been scarcely studied [ 13 , 14 ]. Unripe grapes are a source of natural antioxidants such as polyphenols and resveratrol.…”
Section: Introductionmentioning
confidence: 99%
“…A potential use of unripe grapes in winemaking to reduce the alcohol concentration and pH of wine was investigated by other authors, who observed a partial reduction of alcohol content and simultaneous decrease of pH of both Cabernet Sauvignon and Merlot experimental wines [ 12 ]. Although the bioactive compounds and antioxidant activities of grapes at maturity and by-products of the wine production chain have been the subject of many investigations, unripe grapes and their potential application in the food industry have been scarcely studied [ 13 , 14 ]. Unripe grapes are a source of natural antioxidants such as polyphenols and resveratrol.…”
Section: Introductionmentioning
confidence: 99%
“…white, yellow, and red) were purchased from a local market, while the inner layers of Borettane onions were collected at the Naturello company (Pojana Maggiore, Vicenza, Italia). Juices and distillates were obtained from the peeled onions of white (CB and DB,), yellow (CG and DG) and red (CR and DR) varieties, and from Borettana onion wastes (CBo and DBo) by following the procedures described by Tinello and Lante (2017) and Lante and Tinello (2015), respectively. Onion samples were filtered through a Millipore 0.45μm filter membrane (Merck Millipore, Billerica, MA, USA) and stored at -20 °C in the dark until use.…”
Section: Methodsmentioning
confidence: 99%
“…The pH values were in the range of was approximately of 5.7±0.1 and 6.2±0.2 for onion juices and distillates, respectively. The inhibitory effect of onion juices and distillates as well as 0.05% w/v ascorbic acid (AA, reference inhibitor) on TYR and plant PPOs has been in vitro evaluated according to the spectrophotometric assay of Tinello and Lante (2017). Before measuring the enzyme activity, the freeze-dried enzymes were dissolved in 0.1 M sodium citrate buffer at pH 6.0 for TYR (9,390 U/mL), while at pH 6.0, 6.3, 5.5 for respectively potato (10 mg/mL), fennel (100 mg/mL) and eggplant (50 mg/mL) PPOs.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations